(untitled) (Педагогіка вищої та середньої школи, 2003)
This article reveals peculiarities of introduction of Waldorf pedagogy? into the system of work of modern Ukrainian traditional school. The author considers this pedagogic technology> as a variant of personally oriented approach to organization of up-bringing of youth.